Modelling Of Food Hazard Susceptibility In Komatipoort, South Africa - Khumalo., Nomcebo; Mayo., Aloyce, W.; Munishi, Subira (Tanzania Journal of Engineering and Technology, 2018)
Komatipoort, a small town located at the confluence of Komati and Krokodil rivers, is constantly being hit by floods which affect the residents of this small town as well as the farmers settling along the rivers. This study aimed at mapping the flood hazard and susceptibility through the integration of GIS techniques and hydraulic modeling. Due to inconsistency in the length of streamflow data in the different gauging stations, a Hydrological modeling HBV model, was utilized for modelling runoff in order to extend flow records at station X2HO32 for Komati River. Calibration was conducted using observed data from 1982 to 1993, giving an efficiency value of 65% and validation was done using data from 1993 to 1999, giving an efficiency value of 53%. Flood frequencies were analyzed and flood quantiles were determined at different return periods. HEC-RAS was utilized to simulate the hydraulic parameters of Komati and Krokodil rivers to obtain flood hazard maps. GIS-based multi-criteria analysis techniques were incorporated for flood susceptibility mapping. Hydraulic analysis showed that the floods mostly affect the farms and settlements along the rivers and a small part of the central business district is affected. Flood susceptibility mapping showed that the area is generally highly susceptible to flooding because of a combination of anthropogenic and natural factors. Key words: Flood hazard; Komatipoort; Modelling; South Africa; Susceptibility.